Homoarginine and Cardiovascular Outcome in the Population-Based Dallas Heart Study - Dorothee Atzler; M. Odette Gore; Colby Ayers; Chi-un Choe; Rainer H. Böger; James A. de Lemos; Darren K. McGuire; Edzard Schwedhelm (2014)
Objective— The nonproteinogenic amino acid homoarginine has been postulated to have antiatherosclerotic effects as a weak substrate of nitric oxide synthase. This investigation in the population-based Dallas Heart Study (DHS) aimed to evaluate the association of homoarginine with clinical and subclinical cardiovascular outcomes. Approach and Results— Plasma homoarginine was measured in 3514 participants of the DHS using liquid chromatography-tandem mass spectrometry. Associations between homoarginine and major adverse cardiovascular events and all-cause mortality were analyzed using Cox proportional hazard models adjusting for cardiovascular risk factors. Linear regression was used to assess cross-sectional associations between homoarginine and subclinical cardiovascular disease, including coronary artery calcium measured by electron beam-computed tomography, and aortic plaque burden and aortic wall thickness by MRI. Median age was 43 (interquartile range, 36–52) years, with 56% women and 52% black participants. Median follow-up was 9.4 (9.0–9.8) years. Median plasma homoarginine was 2.80 (2.14–3.54) μmol/L. In multivariable models, higher homoarginine was associated with lower rate of major adverse cardiovascular events (hazard ratio, 0.86; 95% confidence interval, 0.75–0.98) and lower all-cause mortality (hazard ratio, 0.82; 0.73–0.92; per 1 log SD increase in homoarginine). Homoarginine was inversely and independently associated with aortic wall thickness (β-estimate, −0.04; P <0.01) but not with aortic plaque burden and coronary artery calcium. Conclusions— Homoarginine is inversely associated with subclinical vascular disease and with risk for cardiovascular disease events. Additional studies are needed to evaluate whether the regulation of plasma homoarginine could emerge as a novel therapeutic option to improve outcomes in cardiovascular disease.